2008
DOI: 10.1002/cmmi.224
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of angiogenesis using Cadence™ contrast pulse sequencing and targeted contrast agents

Abstract: Low-power multipulse imaging in combination with targeted echistatin-bearing microbubbles facilitated a noninvasive, quantitative evaluation of early angiogenesis during real-time imaging. The addition of high-intensity destructive pulses facilitated estimation of the spatial extent of angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 39 publications
0
81
0
Order By: Relevance
“…15,29 CPS method uses non-linear fundamental frequencies, which results in better spatial resolution and high sensitivity to contrast media, and provides improved tissue subtraction than previous ultrasound perfusion imaging techniques. 30,31 Transversal images of semimembranosus muscles of both limbs were captured after a single bolus (0.5 ml) of SonoVue contrast microbubbles (Bracco, Milan, Italy) with the following parameters at 8.0 MHz: power À16 dB, mechanical index 0.31, CPS gain À10 and depth 20 mm. Measurements were done once a week for the first month and thereafter twice a month, and the imaged area was the same in each time.…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…15,29 CPS method uses non-linear fundamental frequencies, which results in better spatial resolution and high sensitivity to contrast media, and provides improved tissue subtraction than previous ultrasound perfusion imaging techniques. 30,31 Transversal images of semimembranosus muscles of both limbs were captured after a single bolus (0.5 ml) of SonoVue contrast microbubbles (Bracco, Milan, Italy) with the following parameters at 8.0 MHz: power À16 dB, mechanical index 0.31, CPS gain À10 and depth 20 mm. Measurements were done once a week for the first month and thereafter twice a month, and the imaged area was the same in each time.…”
Section: Ultrasound Imagingmentioning
confidence: 99%
“…Then low power non-destructive pulses are applied to image the tMBs, followed by a high power disruptive pulse (flash) to eliminate the MBs within the imaging plane which is again followed by low power pulses to image the residual circulating MBs (Figure 2A). The intensity difference before and after the flash corresponds to the amount of bound tMBs and is a measure for the biomarker concentration [144][145][146][147], as shown in Figure 2A. In such methods the quantification of bound tMBs strongly depends on the injected dose, imaging system gain, and local perfusion [137].…”
Section: Contrast-specific Imaging Techniquesmentioning
confidence: 99%
“…After intravenous injection, direct attachment of α V -targeted microbubbles to the vascular endothelium was evident and was significantly greater than adherence of nontargeted microbubbles. Two studies using a Matrigel plug model of angiogenesis demonstrated that the mAb strategy and the RGD peptide strategy yielded similar results, demonstrating similar efficacy of antibody-and peptide-based targeting strategies [12,16]. Next, in a clinically relevant rat model of chronic ischemia, angiogenesis was assessed by CEU molecular imaging after unilateral iliac artery ligation and after FGF-2 supplementation [17].…”
Section: Contrast-enhanced Ultrasound Molecular Imaging Of Angiogenesismentioning
confidence: 89%